An electrochemical study of Fe1.18Sb1.82 as negative electrode for sodium ion batteries. (10th November 2015) - Tran, C.C.H.; Autret, C.; Damas, C.; Claude-Montigny, B.; Santos-Peña, J.
Highlights: First electrochemical study (including the electrode/electrolyte interface) of a new sodium ion battery electrode based on the Fex Sb2-x solid solution. Cycling properties in sodium half cells are examined in two different electrolyte configurations (with or without fluoroethylenecarbonate additive) and two lowest limit potentials (0.2 and 0 V vs Na/Na + ). Electrode/electrolyte interfaces studied by electrochemical impedance spectroscopy indicate a better quality of the films formed on the electrode in presence of fluoroethylenecarbonate. Despite initial discharge capacities close to 450 mAh g −1, the electrode capacity is not fully recovered in the charge, similarly to FeSb2 . Abstract: The mechanism of the electrochemical reaction between FeSb2 and sodium in sodium half cells has been very recently reported [1, L.Baggetto, H.-Y. Hah, C. E. Johnson, C. A. Bridges, J. A. Johnson, G. M. Veith, Phys.Chem.Chem.Phys. 16 (2014) 9538]. Its electrochemical activity, initially limited, seems based on an incomplete desodiation of Na3 Sb formed during the first discharge and the occurrence of a "Fe4 Sb" alloy inactive in the cell. However, no more than two charge/discharge cycles were shown. With this work we shed light on the sodium ion battery electrode properties of another solid in the Fe-Sb system (Fe1.18 Sb1.82 ). Capacity retention properties in two different electrolyte configurations containing NaClO4 as sodium salt and by setting two cycling voltage limits are shown. A discussion about the impact of an additive such as fluoroethylene carbonate (FEC) in the electrode performance is assisted by applying electrochemical impedance spectroscopy on the electrode/electrolyte interfaces. When the additive is not present in the electrolyte, the occurrence of a surface film onto the electrode particles due to the electrolyte decomposition is noticed at low voltage values (0.3 V vs. Na/Na + ). Further discharge leads to the growth of this layer and conversely to decrease in the charge transfer resistance as several well dispersed metallic products are present in the discharged electrode. Upon charging, the film is firstly decomposed and/or dissolved and the charge transfer resistance increases. Beyond 1.05 V vs. Na/Na +, a second film, of a different nature from the first one appears onto fresh antimony or Fex Sby particles formed from desodiation of poorly crystallized Na3 Sb. When FEC is added to the electrolyte, the interface is influenced at each stage of the discharge or the charge. FEC suppresses the growth of the surface film at low voltages and decreases the charge transfer resistance at any stage. Upon charging beyond 1.05 V vs. Na/Na +, the surface films are less resistive than in the absence of FEC. Therefore, the additive has a constructive effect on the cell capacity retention upon cycling. Finally setting the lowest limit voltage at 0.2 V vs. Na/Na + does not result in an improvement in the capacity retention upon cycling, but halves the capacity values compared to the ones obtained at a 0 V vs. Na/Na + limit voltage.